Right Upper Lobe Torsion after Right Lower Lobectomy: A Rare and Potentially Life-Threatening Complication. (23rd December 2018) - Nakada, Takeo; Tsukamoto, Yo; Yabe, Mitsuo; Misawa, Takeyuki; Akiba, Tadashi; Ohtsuka, Takashi
Abstract : An 84-year-old woman was referred to our institution with suspected right lung cancer. Subsequently, she underwent thoracoscopic right lower lobectomy without mediastinal lymph node dissection. Postoperatively, she complained of dyspnea and developed arterial oxygen desaturation after 12 h and acute respiratory failure (ARF). An emergency chest computed tomography revealed the right upper bronchial stenosis with hilar peribronchovascular soft tissue edema because the middle lung lobe had been pushed upward and forward and the right upper lung lobe had twisted dorsally. Emergency bronchoscopy revealed severe right upper bronchial stenosis with an eccentric rotation and severe edema. The bronchia stenosis was successfully treated with glucocorticoids and noninvasive positive pressure ventilation for ARF.